Australia’s definition of royalties: Overreach or evolution - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2024)
In this article, Ooi and Sadiq examine the Australian Taxation Office’s reasoning for adopting a broad interpretation of royalties amidst various criticisms suggesting it has gone too far and is out of step with internationally accepted principles.